Tubular laminated composite structural battery. (26th May 2021) - Pyo, Jaechan; Park, Hyun-Wook; Jang, Min-Su; Choi, Joo-Seung; Sathish Kumar, Sarath Kumar; Kim, Chun-Gon
Abstract: This paper introduces a polymer-matrix composite-based structural lithium-ion battery system with tubular morphology. Its shape and closed cross-section, fabricated during the autoclave process, allow for high electrochemical performance by controlling the electrode distance and battery environment. To prevent the degradation of the organic liquid electrolyte within this continuous resin polymer system, extra components such as thermoplastic hot melt film, a double glass load-bearing separator, aluminum film, and polydimethylsiloxane were implanted. The electrochemical properties of this manufactured multi-functional structural battery design, named the tubular laminated composite battery (TLCB), were tested with a galvanic cell testing machine. The initial specific capacity of TLCB was found to be approximately 120–130 mAh/g with good cycling performance and steady coulombic efficiency. Furthermore, mechanical load resistance and correlation with electrochemical performance were also assessed under the four-point bending load condition. These results show that the TLCB has the potential to operate as a subsidiary energy storage for future electric vehicle systems with a certain level of structural specific capacity and load-bearing properties. Graphical abstract: Image 1